2008
DOI: 10.1097/tp.0b013e31817ef0f9
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Cardiac Risk After Kidney Transplantation: Experience at One Center and Comprehensive Literature Review

Abstract: Background The cardiac implications of obesity in kidney transplant recipients are not well-described. Methods We examined associations of body mass index (BMI) at transplant with post-transplant cardiac risk among 1,102 renal allograft recipients at a single center in 1991-2004. Cumulative post-transplant incidences of congestive heart failure (CHF), atrial fibrillation (AF), myocardial infarction (MI), and a composite of these cardiac diagnoses were estimated by the Kaplan-Meier method. Bivariate (hazards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 49 publications
1
82
1
1
Order By: Relevance
“…W latach 1991-2004 naukowcy z Włoch i USA przeprowadzili badanie na 1102 biorcach nerki [18,19]. Celem pracy była ocena zależności pomiędzy wskaźnikiem masy ciała (BMI) a ryzykiem wystąpienia zaburzeń kardiologicznych takich jak: zastoinowa niewydolność serca, migotanie przedsionków i zawał mięśnia sercowego u osób poddanych zabiegowi transplantacji.…”
Section: Wstępunclassified
“…W latach 1991-2004 naukowcy z Włoch i USA przeprowadzili badanie na 1102 biorcach nerki [18,19]. Celem pracy była ocena zależności pomiędzy wskaźnikiem masy ciała (BMI) a ryzykiem wystąpienia zaburzeń kardiologicznych takich jak: zastoinowa niewydolność serca, migotanie przedsionków i zawał mięśnia sercowego u osób poddanych zabiegowi transplantacji.…”
Section: Wstępunclassified
“…Initial BMI is an independent predictor for patient death and graft failure, and rates of morbidity (81% vs 89%) are higher and graft survival (71% vs 80%) is significantly reduced in obese RTRs at 5 years after transplantation [100] . Corticosteroids are recognised to cause a gain in weight, which may increase the risks of graft dysfunction and CV events [101] . Overall, the pattern of metabolic abnormalities caused by steroids is very similar to that seen in patients with metabolic syndrome [102] .…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…Early studies had reported poorer kidney transplant outcomes in obese dialysis patients (1)(2)(3)(4), mainly because of cardiovascular (5) and infectious complications such as surgical wound infections (6). However, more recent studies have reported that weight change before transplantation did not correlate with graft loss and death after kidney transplantation (7), although obese recipients develop diabetes mellitus or surgical complications more frequently (6,8 -11).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report, BMI Ն 35 kg/m 2 was the third most common reason to deny transplant waitlisting and affecting 10% of potential renal transplant candidates (14). Because the long-term consequences of obesity after transplantation remain unclear (5,15), it is important to address the potential association between pretransplant body composition and posttransplant outcomes.…”
Section: Introductionmentioning
confidence: 99%